Statistik Ekonomi: Perbandingan Pendapatan UMKM Sebelum dan Sesudah Pandemi - Tuti Supatminingsih; Andi Asti Handayani (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting the national economy, yet they are one of the sectors most impacted by the COVID-19 pandemic. This study aims to analyze the differences in MSME income before and after the pandemic and to uncover the factors influencing their recovery process. The study was conducted using a quantitative approach using a descriptive-comparative method, utilizing secondary data from the Central Statistics Agency (BPS) and the Ministry of Cooperatives and SMEs, as well as primary data through questionnaires and interviews with 100 MSMEs from various business sectors. The results show that MSME revenue experienced a sharp decline from IDR 9.6 quadrillion in 2019 to IDR 8.5 quadrillion in 2020, before beginning to recover in 2021. In the post-pandemic period (2022–2023), MSMEs successfully recovered, with their contribution to Gross Domestic Product (GDP) increasing to 61.07% and the number of business units reaching 66 million, surpassing pre-pandemic levels. However, the recovery has been uneven; medium- sized enterprises (MSMEs) recovered faster than small, micro, and ultra-micro enterprises. Government stimulus programs, broader access to financing, the implementation of digitalization, and the adaptability of business actors are key factors driving this recovery. The research findings are expected to serve as a reference in evaluating and formulating policies to strengthen the resilience and competitiveness of MSMEs in the future.